TINJAUAN YURIDIS TERHADAP TINDAKAN PENGANCAMAN MELALUI MEDIA ELEKTRONIK BERUPA PESAN SINGKAT - Adam Gusti (Universitas 17 Agustus 1945 Samarinda, 2021)
ABSTRACTThreatening is someone's intention to do something that has the goal of harming others. The inadequate readiness of human resources in the use of information technology, both in terms of intelligence and mental readiness, has made the sophistication of this information technology a tool that is prone to be used as a medium for committing crimes or more influencing the birth of new forms of legal action. Threats through electronic media are in principle the same as conventional threats, which only distinguish the means, namely through the internet, so that personal videos and photos are included in electronic information and/or electronic documents sent via short messages which are currently electronic media crimes. Regarding threats through electronic media in the form of short messages, the problems in this study are what are the elements of the offense in the act of threatening through electronic media in the form of short messages as regulated in Law No. 19 of 2016 and Imposing legal sanctions for perpetrators of criminal acts who threaten through electronic media in the form of a short message based on a court decision (Number 159 / Pid.Sus / 2018 / PN Lmg). This research method uses Normative Juridical. The juridical normative research method is an approach based on legal materials by examining theories, concepts, legal principles, and laws and regulations referring to the existing norms in society with the addition of various juridical elements.The conclusion obtained is that the elements of the offense of threatening through electronic media in the form of a short message, namely everyone, intentionally and without rights, distributes and/or makes accessible, information and/or electronic documents, which contain extortion and/or threats, and charges of extortion and/or threats. sanctions, namely 7 (seven) months imprisonment and a fine of Rp. 100,000,000 (one hundred million rupiahs)